Lung Transplantation in a New Era in the Field of Cystic Fibrosis - Wei Huang; Alexander T. Smith; Maksim Korotun; Aldo Iacono; Janice Wang (Life, 2023)
Lung transplantation for people with cystic fibrosis (PwCF) is a critical therapeutic option, in a disease without a cure to this day, and its overall success in this population is evident. The medical advancements in knowledge, treatment, and clinical care in the field of cystic fibrosis (CF) rapidly expanded and improved over the last several decades, starting from early pathology reports of CF organ involvement in 1938, to the identification of the CF gene in 1989. Lung transplantation for CF has been performed since 1983, and CF now accounts for about 17% of pre-transplantation diagnoses in lung transplantation recipients. Cystic fibrosis transmembrane conductance regulator (CFTR) modulators have been the latest new therapeutic modality addressing the underlying CF protein defect with the first modulator, ivacaftor, approved in 2012. Fast forward to today, and we now have a growing CF population. More than half of PwCF are now adults, and younger patients face a better life expectancy than they ever did before. Unfortunately, CFTR modulator therapy is not effective in all patients, and efficacy varies among patients; it is not a cure, and CF remains a progressive disease that leads predominantly to respiratory failure. Lung transplantation remains a lifesaving treatment for this disease. Here, we reviewed the current knowledge of lung transplantation in PwCF, the challenges associated with its implementation, and the ongoing changes to the field as we enter a new era in the care of PwCF. Improved life expectancy in PwCF will surely influence the role of transplantation in patient care and may even lead to a change in the demographics of which people benefit most from transplantation.